Mengatasi Problematika Sains Modern dalam Pembangunan Banten Melalui Pendekatan Ekosistem dan Nilai Budaya Lokal (International Forum of Researchers and Lecturers, 2025)
Development in Banten Province has created conflict in development due to the dominance of a minimalist modern science approach, which prioritizes economic growth while ignoring environmental carrying capacity and socio-cultural values. As a result, Banten faces a serious environmental crisis, as evidenced by high emissions of air pollutants (PM2.5, SO2) and river water pollution by industrial waste. This study aims to analyze the negative impacts of this disorganized model and propose a comprehensive solution framework. This study formulates the Holistic Development Model (HDM). The HDM is a transformative solution that synergistically integrates three pillars: Modern Science (providing technology and data), the Ecosystem Approach (providing a systemic framework and nature-based solutions), and Local Cultural Values ​​(forming the basis of ethics and social motivation) through a Systematic Literature Review and Conceptual-Case Analysis. The implementation of MPH in case studies such as Integrated Coastal Management and Integrated Agriculture demonstrates that this integration produces high-yielding, equitable, and sustainable systems. In conclusion, MPH is a crucial strategy for Banten to shift from destructive development to equitable, resilient, and locally rooted development, making ecosystem health a key measure of success.